Education Using Dental Health Book Media to Increase Dental Health Knowledge in Preschool Children - Rika Alipah; Syifa Yulia Lestari (Journal Center of Excellent : Health Assistive Technology, 2026)
Background: Early childhood to elementary school–aged children are considered a vulnerable group for dental caries due to their limited understanding of the importance of oral and dental health. One effective effort to prevent and manage this problem is the provision of oral and dental health education. The use of attractive and interactive media is an effective approach for delivering information to children. A dental health book is one educational medium that can be utilized in promotive activities to improve children’s knowledge of oral and dental health. Objective: To describe students’ knowledge of oral and dental health before and after educational intervention using a dental health book among kindergarten students at Miftahul Huda, Tangerang, in 2025. Method: This study employed a pre-eksperimental design. The sampling technique used in this study resulted in a total sample of 37 kindergarten students at Miftahul Huda in 2025. Results: The results showed an improvement in students’ knowledge. Before the educational intervention, 17 students (45.9%) were categorized as having poor knowledge. After the intervention, all 37 students (100%) demonstrated good knowledge. Conclusion: There was an increase in students’ knowledge of oral and dental health after education using a dental health book. Prior to the intervention, most students were classified as having poor knowledge, whereas after the intervention, all students achieved a good knowledge category